2014
DOI: 10.1177/039463201402700102
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 Genetic Polymorphism in Neonatal Drug Metabolism: Role and Practical Consequences towards a New Drug Culture in Neonatology

Abstract: The cytochrome P450 superfamily (CYP450) in humans is formed by 57 functional monooxygenases critical for the metabolism of numerous endogenous and exogenous compounds. The superfamily is organized into 18 families and 44 subfamilies. CYP nomenclature is based on the identity of amino acids. The most important functions of the CYP450 are related to metabolism of endogenous compounds, detoxification of exogenous xenobiotics and decomposition of the vast majority of currently used drugs. The expression of CYP450… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 39 publications
0
32
0
1
Order By: Relevance
“…25,26 These variations in blood levels are clinically significant and indicate a need to determine possible genetic influences on metabolism of this drug. 17,39 Genes that influence the metabolism of anticholinergics have been identified, and it is possible that one or more of these candidate genes may contribute to our findings. 20,32,4043 …”
Section: Discussionmentioning
confidence: 95%
“…25,26 These variations in blood levels are clinically significant and indicate a need to determine possible genetic influences on metabolism of this drug. 17,39 Genes that influence the metabolism of anticholinergics have been identified, and it is possible that one or more of these candidate genes may contribute to our findings. 20,32,4043 …”
Section: Discussionmentioning
confidence: 95%
“…Лекарственная тера-пия в неонатальном периоде требует существенных улучшений, в первую очередь в сфере проведения клинических испытаний и разрешения применения ряда лекарственных препаратов у новорожденных. Зачастую неонатологи вынуждены использовать пре-параты, официально не разрешенные к применению у новорожденных, и экстраполировать дозы, приме-няемые у детей и взрослых [43]. Критически важной является интеграция знаний об анатомо-физиологи-ческих особенностях доношенных и недоношенных новорожденных, влиянии патологических состоя-ний, возрастозависимых изменениях, данных фар-макогенетики в клинические исследования.…”
Section: рис 2 учет индивидуальных геномных особенностей в вы-боре unclassified
“…Since the enzymatic activity of certain drug metabolizing enzymes can vary as a function of age and due to numerous developmental and maturation processes, the ontology of those enzymes and the influence of genetic variants on their activity are essential for the accurate prediction of treatment response in children. [1][2][3][4] One of the biggest challenges to treatment in children is the first dose. Clinical essays are far more difficult to carry in children than in adults, and thus, this dose is usually extrapolated by applying scaling approaches to data acquired from dosing essays in adults.…”
Section: Current Perspective On Pediatric Pharmacogenomicsmentioning
confidence: 99%
“…CYP3A7 to CYP3A4 in neonates). [2][3][4] Recent studies demonstrated that genetically guided personalized therapy holds the promise to deliver a safer and more effective treatment in pediatric organ transplantation. [5,6] One well-described example is the dosing of Tacrolimus (TAC), an immunosuppressant used to reduce organ rejection both in pediatric and in adult patients.…”
Section: Current Perspective On Pediatric Pharmacogenomicsmentioning
confidence: 99%